Decreased cortical thickness mediates the relationship between premature birth and cognitive performance in adulthood. Issue 17 (21st August 2020) - Schmitz‐Koep, Benita; Bäuml, Josef G.; Menegaux, Aurore; Nuttall, Rachel; Zimmermann, Juliana; Schneider, Sebastian C.; Daamen, Marcel; Scheef, Lukas; Boecker, Henning; Zimmer, Claus; Gaser, Christian; Wolke, Dieter; et al.
Abstract: Cortical thickness (CTh) reflects cortical properties such as dendritic complexity and synaptic density, which are not only vulnerable to developmental disturbances caused by premature birth but also highly relevant for cognitive performance. We tested the hypotheses whether CTh in young adults is altered after premature birth and whether these aberrations are relevant for general cognitive abilities. We investigated CTh based on brain structural magnetic resonance imaging and surface‐based morphometry in a large and prospectively collected cohort of 101 very premature‐born adults (<32 weeks of gestation and/or birth weight [BW] below 1, 500 g) and 111 full‐term controls at 26 years of age. Cognitive performance was assessed by full‐scale intelligence quotient (IQ) using the Wechsler Adult Intelligence Scale. CTh was reduced in frontal, parietal, and temporal associative cortices predominantly in the left hemisphere in premature‐born adults compared to controls. We found a significant positive association of CTh with both gestational age and BW, particularly in the left hemisphere, and a significant negative association between CTh and intensity of neonatal treatment within limited regions bilaterally. Full‐scale IQ and CTh in the left hemisphere were positively correlated. Furthermore, CTh in the left hemisphere acted as a mediator on the association between premature birth and full‐scale IQ. Results provide evidence that premature born adults have widespread reduced CTh that is relevant for their general cognitive performance. Data suggest lasting reductions in cortical microstructure subserving CTh after premature birth. Abstract : Cortical thickness is supposed to reflect dendritic complexity and synaptic density, which are not only vulnerable to the impact of premature birth but also highly relevant for cognitive performance. Based on structural magnetic resonance imaging, we found reduced cortical thickness in associative cortices predominantly in the left hemisphere, which was relevant for lower general cognitive abilities. Our findings suggest cortical thickness in associative cortices as a functionally relevant target for monitoring and treating adverse effects of human premature birth.